EKSPLORASI POTENSI GURU DAN SISWA (Proses Pembuatan Seragam Batik Karya Siswa di SDN Sanden 2 Bantul, Provinsi Daerah Istimewa Yogyakarta) - Santosa, Rahmad (TABULARASA, 2014)
This study aims to explore, empower and harness the potential of teachers and students. The method used is a class act. This research was conducted in TA 2012-2013, with samples in SDN 2 Sanden, Bantul, Yogyakarta Special Region. The target class action is fourth grade and fifth grade. Research priority action to obtain the product range, the process moves cyclically, between action, reflection and further action, always trying to explore the potential hidden in the environment of teachers and students, as well as teachers and students to minimize the problems that arise, to obtain the work produced. The results of this study indicate that the fourth and fifth grade students succeed; (1) making batik uniforms student work itself, (2) during the process of making a change in teacher-student interaction that leads to an interactive relationship, synergistic, and humanist, (3) developing the learning patterns of affective and psychomotor aspects of education that is intensive, and develop parameters qualitative.